PHYTOCHEMICAL SCREENING AND EVALUATION OF ANTIOXIDANT, ANTIBACTERIAL, AND ANTI-INFLAMMATORY ACTIVITIES OF BAMBUSA VULGARIS LEAF EXTRACTS - Bojjala Sravya, J. Jayanth, Sagi Sowmika, Radha Yadamuri, Muppuru Muni Kesavulu (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
Because of its therapeutic qualities, Bambusa vulgaris, also referred to as yellow bamboo, is frequently used in traditional medicine. Using ethanol and acetone as two distinct solvents, the current study sought to assess the phytochemical makeup and biological activity of Bambusa vulgaris leaf extracts. Key secondary metabolites such as flavonoids, alkaloids, tannins, saponins, carbohydrates, and proteins were detected by preliminary phytochemical screening. For the majority of phytoconstituents, ethanol outperformed the other solvent in terms of extraction efficiency, indicating that it is better suited to solubilize a wide variety of bioactive substances. The phosphomolybdenum assay was used to evaluate the extracts’ antioxidant activity. The results showed that the ethanol extract had a substantially higher total antioxidant capacity than the acetone extract, indicating a stronger capacity to scavenge free radicals. The disc diffusion method was used to assess antibacterial efficacy against two bacterial strains, Streptomyces erythraeus and Bacillus subtilis. In both bacteria, the ethanol extract generated bigger zones of inhibition, indicating more potent antimicrobial action. Additionally, the protein denaturation inhibition assay was used to assess the anti-inflammatory effect. Its substantial anti-inflammatory action was further supported by the results, which demonstrated a clear dose-dependent response with the ethanol extract showing higher suppression of protein denaturation. The study concludes that Bambusa vulgaris is a viable natural medicinal agent source that possesses anti-inflammatory, antibacterial, and antioxidant qualities. A scientific foundation for the use of ethanol in the creation of plant-based pharmaceutical and nutraceutical products was established when it was discovered to be a more efficient solvent for removing bioactive components from Bambusa vulgaris leaves.